Some Remarks on Rousseau, Marx, Croce and Marxism - Rockmore, Tom (Bollettino Filosofico, 2025)
The aim of my article is to reconstruct and evaluate the anti-dogmatic interpretation of Marx by the young Benedetto Croce at the end of the 19th century. In the first part, I will analyse the problematic nature of the law of fall of rate of profit, briefly reconstructing how the young Croce proposed a radically anti-Marxist, albeit not entirely clear, interpretation of the epistemological model adopted by Marx for his economic investigations. From here, Croce’s sharp criticism of Marx's alleged law of the fall of rate of profit. In the second part, therefore, the fundamental limits of this law according to Croce’s interpretation will be clarified. In the final part, we will briefly see how Marx’s “law” of fall of rate of profit attempted, unsuccessfully, to resolve on an economic level the problem originally posed by Rousseau, namely that of the origin of social inequality. Keywords: Croce, Law of Fall of Rate of Profit, Marx, Marxism, Rousseau